Analisis berasaskan GIS terhadap dimensi sosio-ekonomi bagi fenomena penagihan dadah - Nur Aisah Abu Bakar, (2013)
Malaysia is taking various efforts to be a „Drug Free Country‟ by the year 2015. This research is conducted to determine the spatial pattern of drug addict in Pontian District, Johor from 2007 to 2010. This research is also conducted to investigate the spatial relationship between socio-economic aspects and their influence on the drug addict particularly in the selected study area. The variables used in this study consist of new and repeated drug addicts, types of drugs and ages of drug addict. The socio-economic focuses on the types of employment and level of education. The data are analyzed using Mean Center and Standard Deviation Ellipse to assess the mean and spatial pattern of drug addicts in the study area. Then, the analysis involves the use of Getis Ord-G* and Moran’s I to identify the hotspot and coldspot of drug addicts in Pontian District. In contrast, the drug addict data and socio-economic factors were analyzed using Ordinary Least Square (OLS) and Geographically Weighted Regression (GWR) in order to gauge the relationship between the included factors. The research findings show that the distribution pattern of new drug addict occur in the urban and sub-urban areas. On the other hand, the status of repeated drug addicts are identified in the rural areas. The correlation between the new and repeated drug addicts with high school education and the types of employment (agro) show there is random spatial relationship between drug addicts, levels of education and types of work. Therefore, this research is believed to be able to assist in illustrating drug addict phenomena together with its relationship to socio-economic factor spatially. The use of Geographic Information System (GIS) and spatial statistics are good effort to help various goverment sectors especially National Anti Drug Agencies (AADK) and Royal Malaysian Police (PDRM) in monitoring and subsequently combating the spread of drug addicts and subsequently developing a safer environment.